Stratospheric chlorine activation in the Arctic winters 1995/96–2001/02 derived from GOME OClO measurements - Kühl, S.; Wilms-Grabe, W.; Beirle, S.; Frankenberg, C.; Grzegorski, M.; Hollwedel, J.; Khokhar, F.; Kraus, S.; Platt, U.; Sanghavi, S.; von Friedeburg, C. (Elsevier, 2004)
In this article, we present satellite observations of OClO from the years 1995–2002. The focus is on observations of OClO in the Arctic wintertime stratosphere, which are compared to results of the SLIMCAT model and to observations in the Antarctic. In particular, we investigated the beginning and ending of the chlorine activation in the Arctic stratosphere. The Slant Column Densities (SCDs) of OClO increase significantly, when the temperature falls below the threshold for formation of Polar Stratospheric Clouds. The time for decrease of the OClO-SCDs in the deactivation phase (early spring) varies strongly and is related to the degree of denitrification. In the Arctic, chlorine activation can be further increased when there is strong activity of stratospheric mountain waves.